Femtosecond profiling of shaped x-ray pulses. (26th March 2018) - Hoffmann, M C; Grguraš, I; Behrens, C; Bostedt, C; Bozek, J; Bromberger, H; Coffee, R; Costello, J T; DiMauro, L F; Ding, Y; Doumy, G; Helml, W; et al.
Abstract: Arbitrary manipulation of the temporal and spectral properties of x-ray pulses at free-electron lasers would revolutionize many experimental applications. At the Linac Coherent Light Source at Stanford National Accelerator Laboratory, the momentum phase-space of the free-electron laser driving electron bunch can be tuned to emit a pair of x-ray pulses with independently variable photon energy and femtosecond delay. However, while accelerator parameters can easily be adjusted to tune the electron bunch phase-space, the final impact of these actuators on the x-ray pulse cannot be predicted with sufficient precision. Furthermore, shot-to-shot instabilities that distort the pulse shape unpredictably cannot be fully suppressed. Therefore, the ability to directly characterize the x-rays is essential to ensure precise and consistent control. In this work, we have generated x-ray pulse pairs via electron bunch shaping and characterized them on a single-shot basis with femtosecond resolution through time-resolved photoelectron streaking spectroscopy. This achievement completes an important step toward future x-ray pulse shaping techniques.